Antidepressant Mechanism of Traditional Chinese Medicine Formula Xiaoyaosan in CUMS-Induced Depressed Mouse Model via RIPK1-RIPK3-MLKL Mediated Necroptosis Based on Network Pharmacology Analysis - Yan, Zhi-Yi; Jiao, Hai-Yan; Chen, Jian-Bei; Zhang, Kai-Wen; Wang, Xi-Hong; Jiang, You-Ming; Liu, Yue-Yun; Xue, Zhe; Ma, Qing-Yu; Li, Xiao-Juan; Chen, Jia-Xu (Frontiers in Pharmacology, 2021)
Background: Depression is a stress-related disorder that seriously threatens people’s physical and mental health. Xiaoyaosan is a classical traditional Chinese medicine formula, which has been used to treat mental depression since ancient times. More and more notice has been given to the relationship between the occurrence of necroptosis and the pathogenesis of mental disorders. Objective: The purpose of present study is to explore the potential mechanism of Xiaoyaosan for the treatment of depression using network pharmacology and experimental research, and identify the potential targets of necroptosis underlying the antidepressant mechanism of Xiaoyaosan. Methods: The mice model of depression was induced by chronic unpredictable mild stress (CUMS) for 6 weeks. Adult C57BL/6 mice were randomly divided into five groups, including control group, chronic unpredictable mild stress group, Xiaoyaosan treatment group, necrostatin-1 (Nec-1) group and solvent group. Drug intervention performed from 4th to 6th week of modeling. The mice in Xiaoyaosan treatment group received Xiaoyaosan by intragastric administration (0.254 g/kg/d), and mice in CUMS group received 0.5 ml physiological saline. Meanwhile, the mice in Nec-1 group were injected intraperitoneally (i.p.) with Nec-1 (10 mg/kg/d), and the equivalent volume of DMSO/PBS (8.3%) was injected into solvent group mice. The behavior tests such as sucrose preference test, forced swimming test and novelty-suppressed feeding test were measured to evaluate depressive-like behaviors of model mice. Then, the active ingredients in Xiaoyaosan and the related targets of depression and necroptosis were compiled through appropriate databases, while the “botanical drugs-active ingredients-target genes” network was constructed by network pharmacology analysis. The expressions of RIPK1, RIPK3, MLKL, p-MLKL were detected as critical target genes of necroptosis and the potential therapeutic target compounds of Xiaoyaosan. Furthermore, the levels of neuroinflammation and microglial activation of hippocampus were measured by detecting the expressions of IL-1β, Lipocalin-2 and IBA1, and the hematoxylin and eosin (H&E) stained was used to observe the morphology in hippocampus sections. Results: After 6-weeks of modeling, the behavioral data showed that mice in CUMS group and solvent group had obvious depressive-like behaviors, and the medication of Xiaoyaosan or Nec-1 could improve these behavioral changes. A total of 96 active ingredients in Xiaoyaosan which could regulate the 23 key target genes were selected from databases. Xiaoyaosan could alleviate the core target genes in necroptosis and improve the hippocampal function and neuroinflammation in depressed mice. Conclusion: The activation of necroptosis existed in the hippocampus of CUMS-induced mice, which was closely related to the pathogenesis of depression. The antidepressant mechanism of Xiaoyaosan included the regulation of multiple targets in necroptosis. It also suggested that necroptosis could be a new potential target for the treatment of depression.